2022
DOI: 10.53819/81018102t6045
|View full text |Cite
|
Sign up to set email alerts
|

Budgetary Controls and Financial Performance of Micro Finance Institutions (MFIs) in Kenya

Abstract: Micro financing institutions in Kenya showed a high growth rate since they were established in 1997 and legislation passed in 2006 with the micro finance Act which became active in 2008. The research sought to determine exactly how budget controls influence financial performance of micro finance organizations (MFIs) in Kenya. The objectives of the study were to establish the effect of budget planning on the performance of MFIs; to figure out the impact of budget control on the performance of MFIs in Kenya; to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
(9 reference statements)
1
3
0
Order By: Relevance
“…The findings are consistent with the results Kim et al (2023) that indicated that capital structure has a positive and significant effect on the profitability performance of firms. Additionally, the results are in harmony with the results of Kwena et al (2023) which indicated that shareholders equity financing has a statistically significant influence on financial performance of MFIs. Additionally, the results are consistent with the results of previous studies (Shikumou, 2023;Shikumoet al, 2023) which revealed that share capital has a positive and significant effect on financial growth measured by growth in market capitalization.…”
Section: Effect Of Short-term Equity Capital Structure On Financial P...supporting
confidence: 79%
See 1 more Smart Citation
“…The findings are consistent with the results Kim et al (2023) that indicated that capital structure has a positive and significant effect on the profitability performance of firms. Additionally, the results are in harmony with the results of Kwena et al (2023) which indicated that shareholders equity financing has a statistically significant influence on financial performance of MFIs. Additionally, the results are consistent with the results of previous studies (Shikumou, 2023;Shikumoet al, 2023) which revealed that share capital has a positive and significant effect on financial growth measured by growth in market capitalization.…”
Section: Effect Of Short-term Equity Capital Structure On Financial P...supporting
confidence: 79%
“…In the Kenyan context, Kwena et al (2023) examined the influence of capital structure on financial performance of MFIs in Kenya. The results showed that retained earnings financing had a statistically significant influence on financial performance of MFIs.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…The likelihood of budget planning positively effecting financial performance diminishes if budgets are predominantly used for control purposes. The budgetary control process involves authorization, preparation, implementation and evaluation (Kemunto & Cheluget, 2022). This process is instrumental in corporate financial planning, as it provides a framework for monitoring and regulating financial activities within the organization.…”
Section: Background To the Studymentioning
confidence: 99%
“…Financial ratio analysis is a critical tool that enables firms to evaluate their financial health by identifying strengths and weaknesses in their financial performance [10]. In addition to assessing the current financial position of the firm, ratio analysis also helps to identify trends by comparing the firm's current performance with past periods [28]. Moreover, financial ratio analysis is also useful for inter-industry comparisons, allowing firms to benchmark their financial performance against competitors in the same industry [24].…”
Section: Effect Of Financial Ratio On Corporate Performancementioning
confidence: 99%